Open and distance learning for limited internet access in technology and engineering course / Siti Sara Rais, Nur Idawati Md Enzai and Hasnorhafiza Husni - Rais, Siti Sara; Md Enzai, Nur Idawati; Husni, Hasnorhafiza (UiTM Press, 2022)
The 2019 Coronavirus outbreak, or Covid-19 pandemic, has accelerated the deployment of internet technology across various sectors, including education. During the early stages of the Covid-19 pandemic, internet platforms and access services were unsatisfactory, particularly in some areas of Malaysia. However, the internet's platform providers are constantly improving their systems. Today (after two years of the outbreak), there are many reliable instruments available for teaching and learning (T&L). Among the initiatives taken by the Internet service providers (ISPs) are continuous expansion of their coverage area. However, this expansion takes time and huge amount of costs are involved. As a result, we took the idea of manipulating multi-featured Telegram as an alternative for students who do not have good access to the internet. We discuss the features available on Telegram in this article. We adapted the discussion on the application based on the mode of delivery, such as computation, description, activities, and others. Additionally, a survey was undertaken to elicit feedback on Open and Distance Learning (ODL)'s usage of Telegram in the T&L process. It has been demonstrated that the use of Telegram enables them to easily and rapidly acquire educational resources.